The relation of discrete stimuli can be integrated despite the failure of conscious identification. Issue 9 (21st October 2018) - Oxner, Matt; Corballis, Paul M.; Hayward, William G.
ABSTRACT: The integration of the sameness or difference of two unconscious stimuli occurs and affects behaviour without subjective visual consciousness. Yet, intermittent stimulus awareness or a process simpler than integration could also account for these results. In a masked go/no-go task, participants provided or withheld a response based on the same/different relation of two stimuli. Post-trial performance on a discrimination task was used to classify invisible stimuli, providing an objective criterion of awareness. Stimulus pairs with a No-go-associated relation showed reduced and slower responding even when those stimuli were incorrectly discriminated and presumably unconscious. Due to the large set of stimuli, this effect is unlikely to be due to response mapping or action triggers. The integration of the relation of discrete stimuli is a cognitive function that is not dependent upon visual awareness, in the form of conscious identification, to occur.